2021
DOI: 10.1002/hyp.14039
|View full text |Cite
|
Sign up to set email alerts
|

Urban stream temperature patterns: Spatial and temporal heterogeneity in the Philadelphia region, Pennsylvania, USA

Abstract: Stream temperature is a critical water quality parameter that is not fully understood, particularly in urban areas. This study explores drivers contributing to stream temperature variability within an urban system, at 21 sites within the Philadelphia region, Pennsylvania, USA. A comprehensive set of temperature metrics were evaluated, including temperature sensitivity, daily maximum temperatures, time >20 C, and temperature surges during storms. Wastewater treatment plants (WWTPs) were the strongest driver of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…3 ). This pattern demonstrates the strong influence of atmospheric and climatic conditions on water temperature despite the stable, warm temperature of effluent at its point of release ( Beganskas & Toran, 2021 ). Trends in dissolved oxygen levels across seasons were generally opposite to those of temperature, with the lowest values observed in summer; however, this pattern was only significant in three of the six reaches ( Table 2 ; Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3 ). This pattern demonstrates the strong influence of atmospheric and climatic conditions on water temperature despite the stable, warm temperature of effluent at its point of release ( Beganskas & Toran, 2021 ). Trends in dissolved oxygen levels across seasons were generally opposite to those of temperature, with the lowest values observed in summer; however, this pattern was only significant in three of the six reaches ( Table 2 ; Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of longitudinal distance from effluent outfalls on water quality varied widely among measured parameters. Effluent is generally warmer than natural baseflow temperatures, so heat exchange between the atmosphere and stream likely led to longitudinal cooling trends ( Boyle & Fraleigh, 2003 ), especially during winter ( Beganskas & Toran, 2021 ; also see “4.2 Seasonal effects” below). As temperatures cooled, dissolved oxygen levels rose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in other studies, in many cases heat pulses are observed to be generated by contributions from storm sewers, as was observed by Somers et al (2013) and Hester and Bauman (2013). Alternatively, heat pulses may result from contributions of runoff or water ponded on near‐stream impervious surfaces (though most cities work to eliminate such areas) that has been heated by hot pavement (Omidvar et al, 2018), stormwater management ponds or detention basins (Sabouri et al, 2016), or wastewater treatment plants (e.g., Beganskas & Toran, 2021). It also remains unclear whether warmer water in the shallow subsurface that has been heated in the lead up to the event and entering the stream with the first flush of precipitation, could also contribute to these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that stream temperature in urban areas depends substantially on the near‐stream land cover. Riparian buffer zones may cool urban stream temperatures (Arora et al, 2018), whereas effluent from waste water treatment plants is known to raise stream temperatures (Beganskas & Toran, 2021). Furthermore, stormwater control measures can substantially influence stream temperature by impacting urban discharge (Fanelli et al, 2019) as well as the temperature of the added localized runoff (Ouellet et al, 2021; Timm et al, 2020).…”
Section: Introductionmentioning
confidence: 99%